Perbedaan Pemberian Gamat Jelly dan Hidrogel dalam Penyembuhan Luka Kronik pada Tikus Putih - Hartono Hartono (Universitas Muhammadiyah Yogyakarta, 2015)
Background: Sea Cucumber contains many active compounds that have health benefi ts. The ability of therapeutic and medicine eff ects have associated with triterpen glycosides (saponin), chondrointin sulfates, glycosaminoglycan (GAGs), sulfates polysacarida, sterol (glycoside and sulfates) phenolics, cerberosides, lectins, peptides, glycoprotein, glycosphingolipids and essential fatty acids.Objective: To compare the eff ectiveness of sea cucumber jelly and hydrogel in chronic wound healing in the white rats.Method : The research was a quasi-experiment with post test design. The number of samples was 10 rats. The rats were divided into two groups: a group was given sea cucumber jelly treatment and the other group was given hydrogel treatment. Before given treatment, a 1x1 cm wound was made on each rats and then the wound was infected with E. Colli. Wound care was done in every 2 days.Result: There was no signifi cant diff erence between the use of sea cucumber jelly and hydrogel in chronic wound healing in the white rats (p = 0,753). Based on the average of healing period, sea cucumber jelly gave better eff ect than hydrogel (wound with sea cucumber jelly treatment was healed 12 days, and hidrogel in 13 days). DESIGN assessment tool was used to assess the wound.Conclusion: Based on the average of healing period, sea cucumber jelly gave better eff ect than hydrogel. Sea cucumber jelly could be to use as the alternatives dressing.Keywords: chronic wound healing, dressing, sea cucumber jelly, hydrogel.